Human immunodeficiency virus 1 tat protein binds trans-activation-responsive region (TAR) RNA in vitro. - Dingwall, C (1989)
tat, the trans-activator protein for human immunodeficiency virus 1 (HIV-1), has been expressed in Escherichia coli from synthetic genes. Purified tat binds specifically to HIV-1 trans-activation-responsive region (TAR) RNA in gel-retardation, filter-binding, and immunoprecipitation assays. tat does not bind detectably to antisense TAR RNA sequences, cellular mRNA sequences, variant TAR RNA sequences with altered stem-loop structures, or TAR DNA.